METODE LINGUISTIK HISTORIS KOMPARATIF BAGI EPIGRAFI: METODE DAN ANALISIS BAGI GEJALA KEBAHASAAN DALAM PRASASTI BERBAHASA JAWA KUNA - Kayato Hardani (BRIN, 2007)
In the ancient history period of Indonesia, the inscription is one of the results of human culture in the classical period which is moveable in addition to the unmoveable remains in the form of temples and water temple buildings. The existence of inscriptions in macro cannot be separated from the forms of other cultures, such as the form of values, forms of behavior systems and forms of material culture.